Gravitational Vortex Water Turbine (GVWT) conical basin design: the effects of cone angle and outlet diameter on vortex characteristics / Erna Septyaningrum ... [et al.] - Septyaningrum, Erna; Hantoro, Ridho; Mouti, Naufal Khoodi; Rahayu, Wiwit Ria; Banta Cut, Sutardi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
A Gravitational Vortex Water Turbine (GVWT) seems to be a promising technology for low-head hydropower applications. The basin of GVWT plays an important role in the vortex formation as well as its performance. This study aims to analyze the effect of basin design on vortex characteristics in the GVWT. A conical basin is chosen due to the good quality of the vortex. The lab-scale experiment and Computational Fluid Dynamic (CFD) simulation was conducted to gain deeper insight into the effect of cone angle (θ) and basin diameter ratio (d/D) on the vortex characteristic, including air-core diameter, vortex height, and tangential velocity. Both parameters play a major role in regulating the water level and tangential velocity in the basin. The current work shows that the smaller the basin diameter ratio (d/D), the higher the vortex height, leading to a decrease in tangential velocity and vortex strength as the kinetic head is converted to a potential head. Moreover, basin parameters, including the vortex height and tangential velocity, fluctuate due to the variation of cone angle. According to this work, the conical basin with a large cone angle of 20° and a small d/D of 0.2 is suggested, since it produces a vortex with height tangential velocity and vortex height.